Key Drivers of Gen Z Employee Retention in Indonesia's Heavy Equipment Industry - Novanantha, Edith; Febriansyah, Hary (Journal Integration of Management Studies, 2025)
This study explores the key drivers of employee retention among Generation Z workers in Indonesia's heavy equipment industry, a sector undergoing rapid transformation amidst talent shortages and generational shifts. Drawing on the Resource-Based View (RBV) and organizational commitment Theory, the study adopts a sequential explanatory mixed-methods approach. Quantitative data were collected via structured surveys (n = 112), and qualitative insights were gained from semi-structured interviews with HR professionals and Gen Z employees. Regression analysis reveals that career development (β = 0.412, p < 0.01), organizational culture fit (β = 0.379, p < 0.01), and meaningful work (β = 0.328, p < 0.05) significantly influence retention intentions. Thematic analysis further underscores the importance of transparent growth pathways, participatory work environments, and alignment with personal values. Notably, compensation was not a dominant retention factor, reflecting a generational shift toward purpose-driven employment. The study contributes to HRM Theory by contextualizing retention within emerging economies and generational preferences. Practically, it offers actionable strategies for managers to enhance retention, such as fostering inclusive leadership, redefining career planning frameworks, and embedding value alignment in recruitment. Ethical considerations, including participant consent and data confidentiality, were upheld throughout. The findings highlight that retaining Gen Z talent requires not only competitive policies but also authentic organizational purpose and developmental engagement.